THE ROLE OF GUIDE AND LOCAL GOVERNMENT IN IMPROVING TOURISM ACCELERATION IN BANGKA BELITUNG - Zulfikri B Rasuan (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2016)
This research report is designed to find and invistigate the function of tourist guide and local govenment in improving tourism accelaration in Bangka Belitung Province. After getting information from many resaources, the writer can make conclusion what the problem of the hotel are in increasing tourist to come to Bangka Belitung province for enjoying panorama and beach. The writer got information from hotel manager the writer considered it’s a problem because as far as the writer knows the quality and quantity of beach and panorama in Bangka Belitung is very excellent but less of promotion. How to solve this problem ? eventhough the number of local guest increase but the guest from abrod so little. The roles of local guide and government are very important because their roles really need to increse the bangka Belitung tourism. The writer thought how to make a link in the other country like Singapore or Malaysia because from these countries there are many tourists and businessmen want to make conference or just want to spend their holiday in staying in hotel of Bangka Belitung. They can come to Indonesia and especially in Bamgka Belitung province by using a special ship from Sinngapore to Bangka Belitung Province. So Bangka Belitung shoud build a special harbour for it. And the writer thought it is a way tomaka Bangka Belitung famailiar as torism province in the world.